2012
DOI: 10.7314/apjcp.2012.13.8.3645
|View full text |Cite
|
Sign up to set email alerts
|

Manual Liquid Based Cytology in Primary Screening for Cervical Cancer - a Cost Effective Preposition for Scarce Resource Settings

Abstract: Conventional pap smear (CPS) examination has been the mainstay for early detection of cervical cancer. However, its widespread use has not been possible due to the inherent limitations, like presence of obscuring blood and inflammation, reducing its sensitivity considerably. Automated methods in use in developed countries may not be affordable in the developing countries due to paucity of resources. On the other hand, manual liquid based cytology (MLBC) is a technique that is cost effective and improves detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 23 publications
5
43
0
Order By: Relevance
“…It provides better morphology with increased detection of abnormalities and preservation of specimen for cell block and ancillary studies like immunocytochemistry and HPV detection. (Nandini et al, 2012;Moosa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It provides better morphology with increased detection of abnormalities and preservation of specimen for cell block and ancillary studies like immunocytochemistry and HPV detection. (Nandini et al, 2012;Moosa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that in endometrial cancer cases, we need the higher sensitivity Pap smear than normal cases. LBC (physician or self-sampling) which had higher sensitivity than conventional Pap smear should be used as a tool for a better detection of cervical involvement (Nandini et al, 2012;Yoshida et al, 2013;Moosa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For limited-resource, manual liquid based cytologi in primary screening is still preferable (Nandini et al, 2012). In Indonesia, cervical cancer screening programs consists of Pap smears and now visual inspection with acetic acid is also increasing, however, the uptake of screening remains low (Domingo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%